DETERMINAN PERTUMBUHAN EKONOMI INDONESIA: ADAKAH PENGARUH DARI KEBIJAKAN DEFISIT ANGGARAN DAN OTONOMI DAERAH? - Rusydi, Bahrul Ulum; Nurpaida, Ida; Hasbiullah, Hasbiullah (ICOR: Journal of Regional Economics, 2024)
Indonesia's economic growth experienced fluctuations both in the period before and after regional autonomy with less stable levels of budget deficit and inflation. Therefore, this research aims to understand the influence of budget deficits and inflation on economic growth before and after regional autonomy in Indonesia. This type of research is quantitative research with data collection techniques using documentation and literature study methods and using secondary data from the Internet, BPS, World Bank, and the Ministry of Finance. This research applies multiple linear regression analysis using dummy variables with data processing using eviews 12. The research results show that the budget deficit has a positive effect on economic growth, inflation has a negative effect on economic growth and the autonomy period has no effect on economic growth in Indonesia.